Separator for electrochemical device and electrochemical device including the same

By strategically distributing first and second binder particles and inorganic particles in the porous coating layer of the separation membrane, the adhesion between the electrode and the membrane is significantly improved, addressing the challenges faced by existing technologies in maintaining membrane integrity after electrolyte impregnation.

JP2025511443APending Publication Date: 2025-04-16LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024548613
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2023-09-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Existing separation membranes for electrochemical devices face challenges in maintaining adequate adhesion between the electrode and the membrane, especially after the electrolyte is poured, due to insufficient distribution of binder particles relative to inorganic particles.

Method used

The separation membrane incorporates a porous coating layer with a specific distribution of first and second binder particles and inorganic particles, where the inorganic particles are most abundant on the surface facing the porous polymer substrate, and the second binder particles are predominantly on the opposite surface, ensuring enhanced adhesion both in dry and wet states.

Benefits of technology

This configuration achieves excellent adhesion between the electrode and the separation membrane, maintaining integrity even after electrolyte impregnation, thereby enhancing the performance and reliability of electrochemical devices like lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511443000001_ABST
    Figure 2025511443000001_ABST
Patent Text Reader

Abstract

The present invention relates to a separator for an electrochemical device, comprising: a porous polymer substrate; and a porous coating layer formed on at least one side of the porous polymer substrate, the porous coating layer comprising first binder particles, second binder particles, and inorganic particles, the inorganic particles being distributed in the largest amount on a first surface facing the porous polymer substrate, the second binder particles being distributed in the largest amount on a second surface opposite to the first surface, and a weight per particle of the inorganic particles being greater than a weight per particle of each of the first binder particles and the second binder particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention claims the benefit of the filing date of Korean Patent Application No. 10-2022-0112886, filed with the Korean Intellectual Property Office on September 6, 2022, the entire contents of which are incorporated herein by reference. The present invention relates to a separator for an electrochemical device having improved dry adhesive strength and wet adhesive strength, and an electrochemical device including the same. [Background technology]

[0002] Electrochemical devices convert chemical energy into electrical energy by utilizing electrochemical reactions. Recently, lithium secondary batteries have been widely used because of their high energy density, high voltage, long cycle life, and applicability in various fields.

[0003] The lithium secondary battery may include an electrode assembly made of a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, and may be manufactured by housing the electrode assembly in a case together with an electrolyte. The separator is disposed between the positive electrode and the negative electrode to insulate the electrodes, and may include a porous coating layer including a polymer binder and inorganic particles on at least one surface of the porous polymer substrate. The inorganic particles may be connected to other inorganic particles by the polymer binder to form an interstitial volume, and lithium ions may move through the interstitial volume. In addition to fixing the inorganic particles, the polymer binder may provide adhesive strength to the porous coating layer, and the porous coating layer may be attached to the porous polymer substrate and the electrode, respectively.

[0004] A porous coating layer including a polymer binder and inorganic particles can prevent thermal shrinkage of a porous polymer substrate. The porous coating layer can be formed by coating a porous polymer substrate with a slurry including a polymer binder, inorganic particles, and a solvent, and drying the slurry. When the slurry is coated and dried, the solvent volatilizes, causing migration of the polymer binder and inorganic particles. The migration of the polymer binder and inorganic particles can be determined by a combination of factors including the physical properties of the polymer binder and inorganic particles, the physical properties of the slurry, and drying conditions.

[0005] In particular, the physical properties of the polymer binder and the inorganic particles may be the main factors that determine the structure and function of the porous coating layer. For example, by controlling the factors, the polymer binder may be distributed on the opposite surface of the porous polymer substrate in the porous coating layer to ensure the adhesive strength of the separator to the electrode. However, even if the polymer binder is distributed on the surface, if the polymer binder is small in size relative to the inorganic particles, the polymer binder may be sandwiched between the inorganic particles and unable to move, or the binder may not be distributed to the outermost part of the porous coating layer, resulting in insufficient adhesive strength.

[0006] Therefore, research is being conducted on a separator that can prevent a decrease in adhesive strength of the separator including a porous coating layer by controlling the physical properties of the polymer binder and the inorganic particles. Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention provides a separator for an electrochemical device, in which binder particles providing wet adhesion are located on the surface of a porous coating layer, and an electrochemical device including the separator, which has excellent adhesion between an electrode and the separator even after an electrolyte is injected. [Means for solving the problem]

[0008] One aspect of the present invention provides a separator for an electrochemical device, comprising: a porous polymer substrate; and a porous coating layer formed on at least one side of the porous polymer substrate, the porous coating layer comprising first binder particles, second binder particles, and inorganic particles, the inorganic particles being distributed in the largest amount on a first surface facing the porous polymer substrate, the second binder particles being distributed in the largest amount on a second surface opposite to the first surface, and a weight per particle of the inorganic particles being greater than a weight per particle of each of the first binder particles and the second binder particles.

[0009] The weight per particle of the first binder particles may be greater than the weight per particle of the second binder particles, and the weight per particle may be determined from the density and diameter (D50) of each particle before preparing the slurry for forming the porous coating layer.

[0010] At least one of the first binder particles and the second binder particles may be an aqueous binder particle.

[0011] The first binder particles and the inorganic particles are each spherical particles, and the diameter (D50) of the first binder particles may be equal to or larger than the radius of the inorganic particles.

[0012] The second binder particles may be spherical particles, and the diameter (D50) of the second binder particles may be equal to or greater than the radius of the first binder particles.

[0013] The density of the second binder particles may be greater than the density of the first binder particles.

[0014] The first binder particles may provide an adhesive force between the separator for an electrochemical device and an electrode when the separator for an electrochemical device is in a dry state, and the second binder particles may provide an adhesive force between the separator for an electrochemical device and an electrode when the separator for an electrochemical device is immersed in an electrolyte.

[0015] The inorganic particles include Li3PO4, Li x Ti y (PO4)3(0 <x<2、0<y<3)、Li x Al y Ti z (PO4)3(0 <x<2、0<y<1、0<z<3)、Li x La y TiO3(0 <x<2、0<y<3)、Li x Ge y P z S w (0 <x<4、0<y<1、0<z<1、0<w<5)、Li x N y (0 <x<4、0<y<2)、Li x S y S z (0 <x<3、0<y<2、0<z<4)、Li x P y S z (0 <x<3、0<y<3、0<z<7)、Li7La3Zr2O 12 , BaTiO3, BaSO4, Pb(Zr,Ti)O3(PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT, 0 <x<1、0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3(PMN-PT), HfO2, Sb2O3, Sb2O4, Sb2O5, SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, Zn2SnO4, ZnSnO3, ZnSn(OH)6, ZrO2, Y2O3, SiO2, Al2O3, AlOOH, Al(OH)3, SiC, TiO2, H3BO3 and HBO2.

[0016] The porous coating layer may include a polymer binder including the first binder particles and the second binder particles, and the inorganic particles in a weight ratio of 10:90 to 50:50.

[0017] The porous coating layer may include the first binder particles and the second binder particles in a weight ratio of 1:0.5 to 1:1.5.

[0018] The porous coating layer may have a thickness of 1.5 to 5 μm.

[0019] Another aspect of the present invention provides an electrochemical device including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, and the separator may be the separator for an electrochemical device according to the aspect of the present invention.

[0020] The electrochemical device may be a lithium secondary battery. Effect of the Invention

[0021] In the separator for an electrochemical device according to the present invention, inorganic particles, first binder particles, and second binder particles are distributed in this order from the surface of the porous coating layer closest to the porous polymer substrate, and the second binder particles provide wet adhesion even after the separator is immersed in an electrolyte. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a conceptual diagram of a separation membrane according to the present invention.

[0023] [Diagram 2] 2 is an SEM image of the surface of the separation membrane of Example 1.

[0024] [Diagram 3] 1 is an SEM image of the surface of the separation membrane of Example 2.

[0025] [Figure 4] 2 is an SEM image of the surface of the separation membrane of Comparative Example 1.

[0026] [Diagram 5] 1 is an SEM image of the surface of the separation membrane of Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Hereinafter, each component of the present invention will be described in more detail so that a person having ordinary skill in the art to which the present invention pertains can easily implement the present invention. However, this is merely an example, and the scope of the present invention is not limited to the following content.

[0028] As used herein, the term "comprising" is used in listing materials, compositions, devices, and methods useful in the present invention, and is not intended to be limiting to the listed examples.

[0029] As used in this specification, the terms "about" and "substantially" are used to mean a range of values ​​or degrees or similar thereto, taking into consideration inherent manufacturing and material tolerances, and are used to prevent infringers from unfairly exploiting the disclosure content in which precise and absolute values ​​provided to aid in the understanding of the present invention are recited.

[0030] As used herein, the term "electrochemical device" may refer to a primary battery, a secondary battery, a supercapacitor, and the like.

[0031] As used herein, unless otherwise specified, "diameter" refers to D50, which is the diameter that corresponds to 50% in the cumulative particle number distribution by diameter.

[0032] The term "radius" as used herein means a cumulative 50% value from the smallest value calculated based on the results of measuring the particle size (D50) distribution of particles using a general particle size distribution measurement system. For example, the particle size distribution can be determined by dispersing particles in an aqueous solution, stirring the solution using an ultrasonic dispersing device, and then subjecting the particles to laser diffraction or scattering.

[0033] As used herein, the term "majority" refers to the inorganic particles being present in a majority in a first surface region facing the porous polymeric substrate, meaning that the relative amount of inorganic particles present in the first surface region is greater than in other regions of the porous coating layer. That is, the inorganic particles are present in the greatest amount in the first surface region. Similarly, the term "majority" refers to the second binder particles being present in a majority in a second surface region opposite the first surface region, meaning that the relative amount of second binder particles present in the second surface region is greater than in other regions of the porous coating layer. That is, the second binder particles are present in the greatest amount in the second surface region.

[0034] An embodiment of the present invention provides a separator including a porous polymer substrate and a porous coating layer formed on at least one side of the porous polymer substrate, the porous coating layer including first binder particles, second binder particles and inorganic particles, the inorganic particles being distributed in the largest amount on a first surface facing the porous polymer substrate and the second binder particles being distributed in the largest amount on a second surface opposite to the first surface, and the weight per particle of the inorganic particles being greater than the weight per particle of each of the first binder particles and the second binder particles.

[0035] The porous polymer substrate provides pores through which lithium ions can pass while electrically insulating the positive and negative electrodes to prevent short circuits. The porous polymer substrate may be resistant to the electrolyte of the electrochemical device, which is an organic solvent. For example, the porous polymer substrate may include, but is not limited to, polymer resins such as polyolefins such as polyethylene, polypropylene, and polybutene, polyvinyl chloride, polyethylene terephthalate, polycycloolefin, polyethersulfone, polyamide, polyimide, polyimideamide, polyaramid, polycycloolefin, nylon, polytetrafluoroethylene, and copolymers or mixtures thereof. Preferably, the porous polymer substrate includes a polyolefin-based polymer, and has excellent slurry applicability for forming a porous coating layer, which may be advantageous for manufacturing a thin separator.

[0036] The thickness of the porous polymer substrate may be 1 to 100 μm, preferably 1 to 30 μm, and more preferably 15 to 30 μm. The porous polymer substrate may include pores having an average diameter of 0.01 to 10 μm.

[0037] A slurry may be applied to at least one surface of the porous polymer substrate and dried to form a porous coating layer, which will be described later. The slurry may further include a surfactant. The slurry may include first binder particles, second binder particles, inorganic particles, a dispersion medium, etc. Before applying the slurry, the porous polymer substrate may be subjected to a surface treatment, such as a plasma treatment or a corona discharge, in order to improve the impregnation of the electrolyte.

[0038] Examples of the surfactant used in the slurry include nonionic surfactants, ionic surfactants, and amphoteric surfactants, and the specific type of substance can be selected within the range known in the art. For example, the surfactant may include dimethyl silicone, aminosilane, acrylic silane, vinylbenzyl silane, glycidyl silane, mercaptosilane, polydimethylsiloxane, or two or more of these. The content of the surfactant in the slurry may be 0.5 to 1% of the slurry weight.

[0039] The separator for an electrochemical device may include the porous polymer substrate and a porous coating layer. The porous coating layer may be provided on one or both sides of the porous polymer substrate. The porous coating layer may be formed by applying a slurry to at least one side of the porous polymer substrate and drying the slurry.

[0040] The porous coating layer may include inorganic particles for improving mechanical properties and insulating properties of the porous polymer substrate, and a polymer binder for improving adhesion between an electrode and a separator. The polymer binder includes first binder particles and second binder particles, and the polymer binder provides adhesion between the electrode and the separator and can bind adjacent inorganic particles and maintain the bond. The inorganic particles can be bonded to adjacent inorganic particles to provide interstitial volumes, which are pores between the inorganic particles, and lithium ions can move through the interstitial volumes.

[0041] At least one of the first binder particles and the second binder particles may be aqueous binder particles. The weight average molecular weight of the aqueous binder particles may be 10,000 to 10,000,000. Preferably, both the first binder particles and the second binder particles may be aqueous binder particles.

[0042] The first binder particles can provide an adhesive force (dry adhesive force) between the separator and the electrode when the separator is in a dry state. The separator and the electrode can be laminated to manufacture an electrode assembly, and since there is no electrolyte, the dry adhesive force between the separator and the electrode is important. The dry adhesive force, which is the adhesive force of the separator in a dry state, may be 10 gf / 25 mm or more, preferably 10 gf / 25 mm to less than 100 gf / 25 mm, and more preferably 50 gf / 25 mm to less than 100 gf / 25 mm. If the dry adhesive force exceeds 100 gf / 25 mm, it may prevent the electrolyte from permeating the separator, which may cause lithium dendrites to precipitate.

[0043] The second binder particles can provide an adhesive force (wet adhesive force) between the separator and the electrode in a state where the separator is immersed in an electrolyte. The electrode assembly can be inserted into a pouch or case and an electrolyte can be injected to manufacture an electrochemical device. In this case, the separator is immersed in the electrolyte, so the wet adhesive force between the separator and the electrode is important. The wet adhesive force, which is the adhesive force of the separator in a state where it is immersed in the electrolyte, can be 1.0 gf / 20 mm or more, more specifically, 10 gf / 20 mm or more, and more specifically, 7 gf / 20 mm to 20 gf / 20 mm. If the wet adhesive force is less than 1 gf / 20 mm, the stiffness of the cell is reduced, which can cause assembly problems and bending problems of the separator during the manufacture of the electrode assembly, and if it exceeds 20 gf / 20 mm, the impregnation of the electrolyte into the separator is hindered, which can cause lithium dendrites to be precipitated.

[0044] The first binder particles and the second binder particles may be any particles that provide a dry adhesive force and a wet adhesive force, respectively. Preferably, the first binder particles include an acrylic binder and can provide a dry adhesive force between the separator and the electrode. For example, the first binder particles may be one or more selected from the group consisting of styrene-butadiene rubber, nitrile-butadiene rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-styrene rubber, and polymers containing acrylate. Preferably, the second binder particles include a polyvinyl fluoride binder and can provide a wet adhesive force between the separator and the electrode. For example, the second binder particles may be one or more selected from the group consisting of polyvinylidene fluoride, polyhexafluoropropylene, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride-trichloroethylene (PVDF-TCE), polyvinylidene fluoride-chlorotrifluoroethylene (PVDF-CTFE), and polymers containing polyvinylidene fluoride and acrylate.

[0045] The inorganic particles may form a porous coating layer with a uniform thickness and may not undergo an oxidation-reduction reaction within the operating voltage range of an electrochemical device to which the inorganic particles are applied. For example, the inorganic particles may have one or more of the following characteristics: lithium ion transfer ability, piezoelectricity, and flame retardancy.

[0046] The inorganic particles having lithium ion transport ability refer to inorganic particles that contain lithium elements but have the function of transporting lithium ions without storing lithium. The inorganic particles having lithium ion transport ability can transport and move lithium ions through a type of defect present inside the particle structure. This improves the lithium ion conductivity in the electrochemical device, thereby improving the performance of the electrochemical device.

[0047] For example, inorganic particles having lithium ion conduction ability include Li3PO4, Li x Ti y (PO4)3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3 (0 < x < 2, 0 < y < 1, 0 < z < 3), Li x La y TiO3 (0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitrides such as Li3N (Li x N y , 0 < x < 4, 0 < y < 2), SiS2-based glasses such as Li3PO4-Li2S-SiS2 (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5-based glasses such as LiI-Li2S-P2S5 (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), LLZO-based such as Li7La3Zr2O 12 and may be one or more selected from the group consisting of these mixtures, but are not limited thereto.

[0048] Piezoelectric inorganic particles refer to a material that is non-conductive at normal pressure, but when a certain pressure is applied, it conducts electricity due to a change in its internal structure. The inorganic particles may exhibit high dielectric constant characteristics with a dielectric constant of 100 or more, and when a certain pressure is applied and stretched or compressed, charges are generated, one side is positively charged and the other side is negatively charged, so that a potential difference is generated between both sides. When an internal short circuit occurs between the positive and negative electrodes due to an external impact such as a local crush or a nail, the inorganic particles coated on the separator not only prevent the positive and negative electrodes from coming into direct contact with each other, but also generate a potential difference within the particles due to the piezoelectricity of the inorganic particles, and thus electron transfer between the positive and negative electrodes, i.e., a minute current flow, is formed, resulting in a gentle voltage reduction of the electrochemical device and improved safety.

[0049] For example, inorganic particles with piezoelectric properties include BaTiO3, BaSO4, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT)(0 <x<1、0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), HfO2 (hafnia) and mixtures thereof, but are not limited thereto.

[0050] The flame-retardant inorganic particles can impart flame-retardant properties to the separator or prevent a rapid increase in temperature inside the electrochemical device.

[0051] For example, the flame retardant inorganic particles may be, but are not limited to, one or more selected from the group consisting of Sb2O3, Sb2O4, Sb2O5, SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, Zn2SnO4, ZnSnO3, ZnSn(OH)6, ZrO2, Y2O3, SiO2, Al2O3, AlOOH, Al(OH)3, SiC, TiO2, H3BO3, HBO2, and mixtures thereof.

[0052] In the present invention, the inorganic particles, the first binder particles, and the second binder particles may be arranged in order from a surface of the porous coating layer that is closer to the porous polymer substrate by adjusting the correlation of physical properties of the inorganic particles, the first binder particles, and the second binder particles.

[0053] The inorganic particles may be distributed in the largest amount on a first surface of the porous coating layer facing the porous polymer substrate, for example, 50 to 99.99 wt % of the inorganic particles contained in the porous coating layer may be distributed on the first surface.

[0054] The second binder particles may be distributed in the largest amount on a second surface of the porous coating layer, which is opposite to the first surface. For example, 50 to 99.99 wt % of the second binder particles contained in the porous coating layer may be distributed on the second surface. The second binder particles are distributed in the largest amount on the second surface, which corresponds to the outermost portion of the separator, and the separator may exhibit excellent adhesive strength to an electrode when immersed in an electrolyte.

[0055] The density of the inorganic particles may be greater than the density of each of the first binder particles and the second binder particles. The second binder particles may have a greater density than the first binder particles. For example, the density of the inorganic particles may be greater than 3 g / cm. 3 and the density of the second binder particles is 1.1 to 2 g / cm 3 and the density of the first binder particles is 1.2 g / cm3 It may be the following.

[0056] When the slurry is applied to a porous polymer substrate, the inorganic particles can be distributed in the surface direction of the porous polymer substrate due to the density difference of the particles. The first binder particles and the second binder particles can be stacked on the inorganic particles. For example, as shown in FIG. 1, the second binder particles can be stacked on the inorganic particles, and the first binder particles can be stacked on the second binder particles, or the first binder particles and the second binder particles can be randomly distributed and stacked on the inorganic particles.

[0057] The inorganic particles may have a weight per particle greater than the weight per particle of each of the first binder particles and the second binder particles. The first binder particles may have a weight per particle greater than the weight per particle of the second binder particles. During the formation of the porous coating layer, the heaviest inorganic particles are distributed on a first surface facing the porous polymer substrate, and the lightest second binder particles may migrate to the surface of the porous coating layer faster than the first binder.

[0058] The first binder particles and the inorganic particles are each spherical particles, and the diameter of the first binder particles may be equal to or larger than the radius of the inorganic particles. For example, the radius of the inorganic particles may be 250 nm to 2500 nm, and the diameter of the first binder particles may be equal to or larger than the radius of the inorganic particles. If the radius of the inorganic particles is less than 250 nm, a polymer binder is additionally required for bonding between the inorganic particles, which is disadvantageous in terms of electrical resistance. If the radius of the inorganic particles exceeds 2500 nm, the uniformity of the surface of the coating layer is reduced, and the separator and electrodes may be damaged during lamination by the particles protruding after coating, resulting in a short circuit. If the diameter of the first binder particles is smaller than the radius of the inorganic particles, the first binder particles are sandwiched between the inorganic particles, making it impossible to ensure sufficient dry adhesive strength. Preferably, the diameter of the first binder particles may be greater than the radius of the inorganic particles.

[0059] The second binder particles may be spherical particles, and the diameter of the second binder particles may be equal to or larger than the radius of the first binder particles. When the slurry is dried, the dispersion medium contained in the slurry evaporates, which induces the movement of the first binder particles and the second binder particles. The second binder particles, which have a light weight per particle, may move faster than the first binder particles. The second binder particles may move past the first binder particles to the opposite side of the porous polymer substrate, and after moving, the diameter of the second binder particles is larger than the radius of the first binder particles, so that the second binder particles do not move further toward the porous polymer substrate. If the diameter of the second binder particles is smaller than the radius of the first binder particles, the second binder particles are sandwiched between the first binder particles, making it impossible to ensure sufficient wet adhesive strength. Preferably, the diameter of the second binder particles may be larger than the radius of the first binder particles.

[0060] The porous coating layer formed by evaporating the dispersion medium may have a concentration gradient of the second binder particles, the first binder particles, and the inorganic particles from the outermost portion of the porous coating layer toward the porous polymer substrate.

[0061] The second binder particles may be distributed most predominantly on the second surface of the porous coating layer (the area opposite the area facing the porous polymer substrate) and least predominantly on the surface area (first surface) facing the porous polymer substrate.

[0062] The first binder particles may be predominantly distributed in a region between the second surface of the porous coating layer and the first surface facing the porous polymeric substrate.

[0063] The inorganic particles may be distributed most predominantly on a first surface facing the porous polymeric substrate and least predominantly on a second surface of the porous coating layer.

[0064] The second binder particles and the first binder particles are both distributed on the second surface of the porous coating layer, and the second binder particles may be distributed in a greater amount than the first binder particles. For example, 10 to 50% by weight of the first binder particles contained in the porous coating layer may be distributed on the second surface. The first binder particles distributed on the second surface of the porous coating layer may provide a dry adhesive force, and the second binder particles distributed on the second surface of the porous coating layer may provide a wet adhesive force.

[0065] The porous coating layer may contain a polymer binder including the first binder particles and the second binder particles and the inorganic particles in a weight ratio of 10:90 to 50:50. If the polymer binder is contained less than this range, the porous coating layer may peel off from the porous polymer substrate or sufficient adhesive strength between the electrode and the separator may not be ensured, and if the polymer binder content exceeds this range, the cell resistance may become too high.

[0066] The porous coating layer may include the first binder particles and the second binder particles in a weight ratio of 1:0.5 to 1:1.5. If the second binder particles are included in an amount less than this range, the adhesion between the electrode and the separator cannot be maintained when the layer is immersed in the electrolyte. If the second binder particles are included in an amount exceeding this range, the second binder particles are not sufficiently distributed on the surface (e.g., the second surface) of the porous coating layer, and the adhesion between the electrode and the separator cannot be maintained when the layer is immersed in the electrolyte.

[0067] The thickness of the porous coating layer may be 1.5 μm to 5 μm. If the thickness of the porous coating layer is less than 1.5 μm, the wet adhesive strength is significantly reduced, and a problem occurs in which the electrode and the separator are separated when an electrolyte is injected. If the thickness of the porous coating layer exceeds 5 μm, the adhesive strength between the separator and the electrode does not increase significantly.

[0068] The porous coating layer may further include a dispersant to further improve the dispersibility of the inorganic particles. The dispersant functions to maintain the inorganic particles in a uniformly dispersed state in the polymer binder during the preparation of the slurry. For example, the dispersant may be any one or more selected from the group consisting of oil-soluble polyamines, oil-soluble amine compounds, fatty acids, fatty alcohols, sorbitan fatty acid esters, tannic acid, and pyrogallic acid. When the slurry includes a dispersant, the porous coating layer may include the dispersant in an amount of 5 wt % or less.

[0069] Another embodiment of the present invention provides an electrochemical device including a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the separator is the separator for an electrochemical device according to the above-described embodiment.

[0070] The positive electrode and the negative electrode may be formed by applying an active material to at least one surface of each current collector and drying it. The current collector may be a material having electrical conductivity without inducing a chemical change in the electrochemical element. For example, the positive electrode current collector may be, but is not limited to, aluminum, nickel, titanium, calcined carbon, stainless steel, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. For example, the negative electrode current collector may be, but is not limited to, copper, nickel, titanium, calcined carbon, stainless steel, or copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. The current collector may be in various forms such as a metal thin plate, a film, a foil, a net, a porous body, a foam, or the like.

[0071] For example, the positive electrode active material is lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2); 1+x Mn 2-x Lithium manganese oxides such as LiMnO4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-x M x Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01 to 0.3); 2-x M x The lithium manganese composite oxides may include, but are not limited to, lithium manganese oxides represented by Li2Mn3MO8 (wherein M is Co, Ni, Fe, Cr, Zn, or Ta, and x is 0.01 to 0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; disulfide compounds; Fe2(MoO4)3, and the like.

[0072] The negative electrode active material is carbon such as non-graphitizable carbon and graphite-based carbon; Lix Fe2O3 (0 ≦ x ≦ 1), Li x WO2 (0 ≦ x ≦ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, 2, 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials, etc. may be included, but are not limited thereto.

[0073] The electrolytic solution may be a non-aqueous electrolytic solution containing a lithium salt. The electrolytic solution consists of an electrolytic solution and a lithium salt. As the electrolytic solution, a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, etc. may be used.

[0074] Examples of the non-aqueous organic solvent include non-quantum organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydroxyfuran (franc), 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivative, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivative, tetrahydrofuran derivative, ether, methyl propionate, ethyl propionate, etc. may be used.

[0075] As the organic solid electrolyte, for example, a polyethylene derivative, a polyethylene oxide derivative, a polypropylene oxide derivative, a phosphate ester polymer, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, a polymerization agent containing an ionic dissociation group, or the like may be used.

[0076] As the inorganic solid electrolyte, for example, nitrides, halides, and sulfates of Li such as Li3N, LiI, Li5NI2, Li3NLiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2 may be used.

[0077] The lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte, such as LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium 4-phenylborate, imide, etc. may be used.

[0078] The electrochemical device may be manufactured by inserting a positive electrode, a negative electrode, a separator, and an electrolyte into a case or pouch and sealing the case or pouch. The shape of the case or pouch is not limited. For example, the electrochemical device may be a cylindrical, rectangular, coin, or pouch-type lithium secondary battery.

[0079] The lithium secondary battery may be packed or modularized as a unit cell and used in small devices such as computers, mobile phones, and power tools; power tools that are driven by a battery-type motor; electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like; electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and medium- to large-sized devices such as power storage systems.

[0080] The present invention will be described in more detail below with reference to specific examples and experimental examples. The following examples and experimental examples are provided to illustrate the present invention, and the present invention is not limited to the following examples and experimental examples.

[0081] Examples 1 and 2

[0082] Slurry preparation

[0083] At room temperature, in distilled water, the density (g / cm 3 ), diameter (nm) and weight per particle (×10 -14 g) and a dispersant were added, and then bead milling was performed (0.7 μm zirconia beads were added in the same amount as the inorganic particles, and milled for 2 hours using a paint shaker) to prepare an inorganic dispersion. The density (g / cm3) of the prepared inorganic dispersion was calculated as shown in Table 1 below. 3 ), diameter (nm) and weight per particle (×10 -14g) was added. In this case, the first binder particles and the second binder particles were added as the polymer binder in the weight ratio shown in Table 1, and a surfactant was added to improve wettability with the substrate. A styrene-butadiene copolymer was used as the first binder, PVDF-butyl acrylate was used as the second binder, and dimethyl silicone (0.5 wt % of the slurry) was used as the surfactant. The mixture was stirred at 10 rpm for 10 minutes to produce a slurry in which the binder particles and inorganic particles were dispersed.

[0084] Preparation of porous polymer substrates

[0085] As the porous polymer substrate, a polyethylene film (PE) having a thickness of 9 μm was used.

[0086] Separation membrane manufacturing

[0087] The slurry was coated on both sides of a polyethylene film using a doctor blade and then dried using a hot air blower to form a porous coating layer with a thickness of 2.5 μm for each coating, thereby producing a separator with a total thickness of about 14 μm.

[0088] Comparative Examples 1 to 5

[0089] Separation membranes were manufactured in the same manner as in Examples 1 and 2, except that inorganic particles and polymer binders having densities, diameters and weights per particle as shown in Table 1 below were used in preparing the slurry. In Comparative Examples 1 to 3, only the first binder particles were used as the polymer binder.

[0090] Experimental example 1. Confirmation of the adhesive strength of the separation membrane

[0091] The dry adhesive strength and wet adhesive strength of the separation membranes according to Examples 1 and 2 and Comparative Examples 1 to 5 were confirmed and are shown in Table 1 below.

[0092] Dry adhesive strength

[0093] A separator measuring 2 cm x 6 cm was laminated on one side of a negative electrode measuring 2.5 cm x 6 cm, and pressurized at 6.5 MPa for 1 second at 60°C. Then, using a Universal Test Machine (Instron) (UTM), the negative electrode was fixed and the separator was peeled off in a 180° direction at a speed of 300 mm / min to measure the peel strength (gf / 25 mm).

[0094] Wet adhesive strength

[0095] A separator of the same size was laminated on one side of a positive electrode measuring 2 cm x 6 cm, and pressurized at 60°C and 6.5 MPa for 1 second. The positive electrode was then inserted into a pouch, and 1.0 g of electrolyte (EC / EMC 3:7 containing LiPF61.0M) was poured into the pouch, followed by leaving the pouch at room temperature for one day.

[0096] The laminate of the positive electrode and the separator was removed from the pouch and pressurized at 5 kgf for 5 minutes at 70°C, and then left at room temperature for 1 hour. After that, the positive electrode was fixed using a UTM, and the separator was peeled off in a 90° direction at a rate of 200 mm / min to measure the peel strength (gf / 20 mm).

[0097] [Table 1]

[0098] Experimental example 2. Confirmation of the surface condition of the separation membrane

[0099] The surfaces of the separation membranes according to Examples 1 and 2 and Comparative Examples 1 and 5 were observed by SEM and are shown in Figures 2 to 5. In the comparative example, it was confirmed that the binder particles were sandwiched in the spaces between the inorganic particles and the binder could not be well distributed on the surface.

[0100] In Comparative Example 4, the second binder particles had a higher density than the first binder particles, and the second binder particles could not be distributed on the surfaces of the first binder particles (surfaces of the separation membrane).

[0101] In Comparative Example 5, the diameter of the second binder particles was too small, so the second binder particles were sandwiched between the first binder particles (or inorganic particles), and the second binder particles could not be distributed on the first binder particles.

[0102] Thus, in Comparative Examples 4 and 5, the wet adhesive strength was relatively low at 2 gf / 20 mm and 3 gf / 20 mm, respectively.

[0103] FIG. 4 for Comparative Example 1 shows that some of the first binder particles, which have a diameter smaller than that of the inorganic particles, are distributed on the inorganic particles, and some of the first binder particles are sandwiched between the inorganic particles.

[0104] FIG. 5 for Comparative Example 5 shows that the first and second binder particles are distributed on the inorganic particles, and the inorganic particles are not observed. In addition, the diameter of the second binder particles is too small, so the second binder particles are sandwiched between the first binder particles. FIG. 5 shows that the second binder particles are not well distributed in the separator.

Claims

1. The present invention includes a porous polymer substrate and a porous coating layer formed on at least one surface of the porous polymer substrate, The porous coating layer comprises: comprising first binder particles, second binder particles and inorganic particles; the inorganic particles are distributed in the largest amount on a first surface facing the porous polymer substrate, and the second binder particles are distributed in the largest amount on a second surface opposite to the first surface; A separator for an electrochemical device, wherein the inorganic particles have a weight per particle greater than a weight per particle of each of the first binder particles and the second binder particles.

2. The separator for an electrochemical device according to claim 1 , wherein the weight per particle of the first binder particles is greater than the weight per particle of the second binder particles.

3. The separator for an electrochemical device according to claim 1 , wherein at least one of the first binder particles and the second binder particles is an aqueous binder particle.

4. the first binder particles and the inorganic particles are each spherical particles, 2 . The separator for an electrochemical device according to claim 1 , wherein a diameter (D50) of the first binder particles is equal to or larger than a radius of the inorganic particles.

5. the second binder particles are spherical particles, The separator for an electrochemical device according to claim 4 , wherein a diameter (D50) of the second binder particles is equal to or larger than a radius of the first binder particles.

6. The separator for an electrochemical device according to claim 5 , wherein the second binder particles have a density greater than a density of the first binder particles.

7. The first binder particles provide an adhesive force between the separator for an electrochemical device and an electrode when the separator for an electrochemical device is in a dry state, 2. The separator for an electrochemical device according to claim 1, wherein the second binder particles provide an adhesive force between the separator for an electrochemical device and an electrode when the separator for an electrochemical device is immersed in an electrolyte.

8. The inorganic particles are Li 3 2O 4 、 x Ti y (2O 4 ) 3 (0<8<2、0<y<3),L- x Al y Ti z (2O 4 ) 3 (0<x<2、0<y<1、0<z<3), L- x Lạ y TiO 3 (0<8<2、0<y<3),L- x Ge y P z S w (0<x<4、0<y<1、0<z<1、0<w<5), L. x N y (0<8<4、0<y<2), L- x Si y S z (0<x<3、0<y<2、0<z<4), L. x P y S z (0<x<3、0<y<3、0<z<7), L- 7 Lạ 3 Zr 2 O 12 、BTT9O 3 、BBO 4 、Pb(Zr,Ti)O 3 (PZT), Pb 1-x Lạ x Zr 1-y Ti y O 3 (>^ZT、0<8<1、0<y<1), Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PMN-PT), HfO 2 、Sb 2 O 3 、Sb 2 O 4 、Sb 2 O 5 、SrTiO 3 、SnO 2 、CeO 2 、MgO、Mg(OH) 2 , NiO, CaO, ZnO, Zn 2 SnO 4 , ZnSnO 3 , ZnSn(OH) 6 , ZrO 2 , Y 2 O 3 , SiO 2 , Al 2 O 3 , AlOOH, Al(OH) 3 , SiC, TiO 2 , H 3 B.O. 3 and H.B.O. 2 2. The separator for an electrochemical element according to claim 1, which is one or more selected from the group consisting of:

9. The porous coating layer comprises:

2. The separator for an electrochemical device according to claim 1, comprising a polymer binder including the first binder particles and the second binder particles and the inorganic particles in a weight ratio of 10:90 to 50:

50.

10. The porous coating layer comprises:

2. The separator for an electrochemical device according to claim 1, wherein the first binder particles and the second binder particles are contained in a weight ratio of 1:0.5 to 1:1.

5.

11. The porous coating layer comprises:

2. The separator for electrochemical devices according to claim 1, having a thickness of 1.5 to 5 μm.

12. An electrochemical device comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, An electrochemical element, wherein the separator is the separator for electrochemical elements according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Separator and method of manufacturing the same, and lithium secondary battery including the separator

    JP2013235824A

  • Separator for power storage device, and electrochemical element

    JP2016072197A

  • Separator and electrochemical element including same

    JP2020507188A

  • Separator with a layer of binder polymers for electrochemical device and Electrochemical device comprising the same

    KR1020160069386A

  • Separator for non-aqueous secondary battery, and non-aqueous secondary battery

    WO2020246497A1